WORDS THAT BIND: INVESTIGATING LEXICAL COHESION IN DISCOURSE - Abubakar, Aisha Fatima; Usman , Suleiman Bala; Aliyu, Zainab Musa (Top Linguistic and Language Journal (TLLJ), 2023)
This paper presents a comprehensive review of lexical cohesion studies in discourse analysis. The paper focuses on the theoretical, developmental and practical application of lexical cohesion in discourse studies. Cohesion is concerned with the linguistic resources on the surface of texts that signal relations between parts of texts. Its textual elements give texts their texture, making them powerful and effective pieces of language. The paper explores the emergence and nature of cohesion in discourse analysis, scholarly rhetoric, and debate on cohesion and textuality in discourse, approaches to lexical cohesion analysis, and insights from lexical cohesion studies. The review is structured into four major sections: (1) emergence and nature of cohesion in discourse analysis, (2) scholarly rhetoric and debate on cohesion and textuality in discourse, (3) approaches to lexical cohesion analysis, and (4) insights from lexical cohesion studies. The paper concludes by highlighting the significance of lexical cohesion as an approach to discourse analysis, revealing its potentials for analyzing different registers and genres (spoken and written) and how it facilitates the perception of relevance of the texts to the intended audience. Ultimately, the study seeks to contribute to the knowledge base of lexical cohesion by providing researchers and students an up-to-date overview of lexical cohesion as an approach to discourse analysis.